Pompom Box Toy to Develop Numeracy Skills in Early Childhood - Dandia Ayu Saraswati; Issaura Dwi Selvi (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
Play supports the development of children’s personalities and essential competencies. The study aimed to develop the pompom box toy to build numeracy skills and investigate psychological and sociological aspects in facilitating the improvement of summation literacy in early childhood. The research employed mix method with the Rowntree model and Tessmer formative evaluation. The Observation was used to collect the data. The results prove that the number addition operation game tool (1-10) in group B children in kindergarten is valid and practical. Its practical value reaches 93.5, with an efficient category based on the child's ability indicator. The child can say number symbols (1-10), and can use the play tool easily. Pompom box learning results in the increase of summation literacy and the development of aspects of early childhood psychology and sociology. The study suggests the exploration of other models of the game, which may give positive impacts on the growth of their attitude, knowledge, and skills.